RELIGIOUS AND HARMONIOUS VALUES IN THE PASAMBAHAN TRADITION AND CEREMONIAL ORATION OF BATAGAK GALA PENGHULU (BGP) IN MINANGKABAU - Mahmudah Nur (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
The Pasambahan Tradition Ceremonial Oration of Batagak Gala Penghulu (BGP) in Minangkabau reflects the communal identity of the Minangkabau society, particularly in communicating, making dialogs and being in dynamics based on the demand of democratic values as understood by the people of the Minangkabau. Thus, through pasambahan tradition, the process of education in good characters and manners is created, which can explicitly be seen through negotiation activity (bapasambahan). To identify the religious and harmonious values, the author examined pasambahan text and ceremonial oration of BGP which were written for learning purposes by Musdah Dahrizal (Mak Katik) by taking some stanza/lines in the text that show religious and harmonious values. The folklore and semiotics approaches are used in analyzing the religious and harmonious values based on reasoning of the people of Minang in accordance with the customs which are used on daily basis. This research reveals that the tradition of pasambahan and ceremonial oration in BGP have essential positions in the custom of the Minangkabau, where the tradition is a depiction of the identity of the Minang clan. The traditions reflect religious and harmonious values which can be seen in the form and content of the pasambahan tradition and ceremonial oration in BGP in Minangkabau, such as inferiority, fairness, politeness, inclusion of religious symbols, mutual cooperation, deliberation, and mutual respect among clans.